PABPN1 Couples the Polyadenylation and Translation of Maternal Transcripts to Mouse Oocyte Meiotic Maturation - Xing‐Xing Dai; Yu‐Ke Wu; Shuai‐Bo Pi; Feng‐Jie Hu; Yun‐Wen Wu; Hang Qi; Zhiyi Li; Zhi‐Yan Jiang; Long‐Wen Zhao; Heng‐Yu Fan (Advanced Science)
Abstract During oocyte meiosis, maternal transcript polyadenylation is crucial for regulating mRNA stability and translation, which are essential for oocyte maturation. Polyadenylate‐binding protein nuclear 1 (PABPN1) plays a key role in regulating mRNA splicing and polyadenylation in somatic cells and growing oocytes. However, its potential function in regulating the meiotic maturation of fully grown oocytes remains unknown. This study reports that selective Pabpn1 knockout in growing mouse oocytes using Zp3‐Cre do not affect folliculogenesis but prevented germinal vesicle breakdown in fully grown oocytes, impaired CDK1 activation, and resulted in abnormal spindle formation and chromosome misalignment. The results of poly(A)‐inclusive full‐length RNA isoform sequencing (PAIso‐seq) and transcriptome sequencing revealed that PABPN1 coordinates meiotic maturation‐coupled polyadenylation and degradation of maternal mRNAs, which are key factors of maturation‐promoting factor (MPF) and deadenylation mediators, such as B‐cell translocation gene‐4 (BTG4), ensuring proper meiotic progression. The results of rescue experiments indicate these functions of PABPN1 are mediated by its key domains, which interact with poly(A) polymerase and recruit target mRNAs. This study highlighted the physiological importance of cytoplasmic PABPN1 in mammalian oocyte maturation by integrating maternal transcript polyadenylation, translation, and degradation.